Combined Effects of Surface Charge and Pore Size on Co-Enhanced Permeability and Ion Selectivity through RGO-OCNT Nanofiltration Membranes - Zhang, Haiguang; Quan, Xie; Chen, Shuo; Fan, Xinfei; Wei, Gaoliang; Yu, Hongtao (Environmental science & technology, 2018)
Nanofiltration (NF) has received much attention for wastewater treatment and desalination. However, NF membranes generally suffer from the trade-off between permeability and selectivity. In this work, the coenhancement of permeability and ion selectivity was achieved through tuning the surface charge and pore size of oxidized carbon nanotube (OCNT) intercalated reduced graphene oxide (RGO) membranes. With the increase of OCNT content from 0 to 83%, the surface charge and the pore size were increased. The permeability increased to 10.6 L m–2 h–1 bar–1 and rejection rate reached 78.1% for Na2SO4 filtration at a transmembrane pressure of 2 bar, which were 11.8 and 1.3 times higher than those of pristine RGO membrane. The composite membrane also showed 11.1 times higher permeability (11.1 L m–2 h–1 bar–1) and 2.9 times higher rejection rate (35.3%) for NaCl filtration. The analyses based on Donnan steric pore model suggest that the increased permeability is attributed to the combined effects of enlarged pore size and increased surface charge, while the enhanced ion selectivity is mainly dependent on the electrostatic interaction between the membrane and target ions. This finding provides a new insight for the development of high-performance NF membranes in water treatment and desalination.